2005
DOI: 10.4049/jimmunol.175.9.5596
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: MyD88 Controls Phagocyte NADPH Oxidase Function and Killing of Gram-Negative Bacteria

Abstract: MyD88 is an adaptor protein for the TLR family of proteins that has been implicated as a critical mediator of innate immune responses to pathogen detection. In this study, we report that MyD88 plays a crucial role in killing Gram-negative bacteria by primary macrophages via influencing NADPH oxidase function. Peritoneal macrophages from MyD88−/− mice exhibited a marked inability to kill Escherichia coli (F18) or an attenuated strain of Salmonella typhimurium (sseB) in vitro. This defect in killing was due to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
127
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(139 citation statements)
references
References 20 publications
(25 reference statements)
8
127
1
3
Order By: Relevance
“…It was shown that NADPH oxidase 4 isozyme directly interacts with TLR4 in human embryonic kidney cells transfected with TLR4, MD-2, and CD14 (51). However, it was shown that MyD88, the downstream component of TLR4, controls NADPH oxidase function in primary macrophages (52). Thus, it is not clear where NADPH oxidase is located in the hierarchical order of TLR4 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that NADPH oxidase 4 isozyme directly interacts with TLR4 in human embryonic kidney cells transfected with TLR4, MD-2, and CD14 (51). However, it was shown that MyD88, the downstream component of TLR4, controls NADPH oxidase function in primary macrophages (52). Thus, it is not clear where NADPH oxidase is located in the hierarchical order of TLR4 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Animals having deficient NADPH oxidase activity have impaired NF-B activation and are more susceptible to infection with P. aeruginosa (14). Additional evidence for interaction between TLR signaling and NADPH oxidase activity was provided recently by showing that MyD88 influences NADPH oxidase assembly and NAPDH oxidase-mediated production of superoxides (36). The expression of several NF-B-dependent genes, including IL-1, IL-6, and Nos2, was shown to be down-regulated in MOLF/Ei mice compared with C57BL/6J mice during infection, suggesting that the Ity3 locus may have an impact on the expression of several proinflammatory genes (17).…”
Section: Ncf2 Encodes For P67mentioning
confidence: 91%
“…In contrast, in the present study, we show that SIRL-1 does not affect intracellular ROS production in neutrophils following challenge with opsonized S. aureus. It has been shown that TLR signaling cooperates with FcRs in the killing of intracellular bacteria by promoting assembly and thus activity of the Nox complex (52). Most likely, signaling through SIRL-1 is not able to suppress synchronized FcR and TLR engagement and the resulting synergistic activation of Nox-2 in neutrophils.…”
Section: Discussionmentioning
confidence: 99%